2016
DOI: 10.11114/afa.v3i1.1932
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Direct Investment (Fdi) On the Stock Market Performances in Nigeria (1985-2014)

Abstract: The study examined the impact of Foreign Direct Investment (FDI) on the stock market performances in Nigeria, from 1985 – 2014. The secondary data used were collected from IMF, International Financial Statistics (2015), CBN Statistical Books (2015). Multiple regression of least square estimation was the tool used to analyze the data in this study.  In the model, the FDI was regressed on RGDP, Consumer Price Index, Real effective exchange rate, Money supply (M2), Share price index, Treasury bill, Nigerian stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Domestic investment, which includes both private and public investment, according to Olise et al (2013), is a critical component of overall investment. FDI, on the other hand, FDI was defined by Onyinyechi and Ekwe (2017) as the net inflow of investment made to acquire a long-term stake (10% or more voting shares) in a business operating in a country other than the investor's. FDI and domestic investment are likely to have a negative connection.…”
Section: Data Measurement and Sourcementioning
confidence: 99%
“…Domestic investment, which includes both private and public investment, according to Olise et al (2013), is a critical component of overall investment. FDI, on the other hand, FDI was defined by Onyinyechi and Ekwe (2017) as the net inflow of investment made to acquire a long-term stake (10% or more voting shares) in a business operating in a country other than the investor's. FDI and domestic investment are likely to have a negative connection.…”
Section: Data Measurement and Sourcementioning
confidence: 99%
“…Expanding the argument of macroeconomic determinants is the supposition that, the official exchange rate of a nation is an important element in determining FDI inflows, which is applicable in some research studies (Ang, 2008;Baby & Sharma, 2017;Bekana, 2016;Dua & Garg, 2015;Ezeoha & Cattaneo, 2012;Naanwaab & Diarrassouba, 2015;Oladipo, 2013;Omodero & Ekwe, 2017;Wafure & Nurudeen, 2010). Dua and Garg (2015), for instance, had previously commented on the host nation's currency depreciation regarding its exchange rates.…”
Section: Macroeconomic Determinants Of Fdimentioning
confidence: 99%
“…The analysis concluded that interest rates and crude oil had a detrimental effect on the stock index. Onyinyechi & Ekwe (2016) conducted comparable research on the Nigerian stock market. Secondary data collected between 1985 and 2014 were analyzed using multiple regression analyses.…”
Section: Literature Review Stock Exchange and Foreign Direct Investmentmentioning
confidence: 99%